Susceptibility to Aneuploidy in Young Mothers of Down Syndrome Children - Lucia Migliore; Francesca Migheli; Fabio Coppedè (The Scientific World Journal)
We recently observed an increased frequency of binucleated micronucleated lymphocytes in women who had a Down syndrome (DS) child before 35 years of age and the fluorescence in situ hybridization analysis revealed that micronuclei were mainly originating from chromosomal malsegregation events, including chromosome 21 malsegregation. That study indicated that women who have a DS child at a young age might have a genetic predisposition to chromosome malsegregation in both somatic and germ line cells. Further studies from our group confirmed increased chromosome damage in blood cells of women who had a DS child at a young age and pointed to a possible role for polymorphisms in folate-metabolizing genes in affecting both chromosome damage and DS risk. In the present article, we review the most recent findings on mechanisms and risk factors for chromosome 21 nondisjunction that lead to DS. Multiple risk factors are likely involved in chromosome nondisjunction; they act at different times in the meiotic process and can be of genetic or environmental (epigenetic) origin. We also discuss the increased risk of developing Alzheimer's disease (AD) later in life that was observed in women who had a DS child at a young age. Studies performed in the last years that have shown that the brain is, in fact, a complex genetic mosaic of aneuploid and euploid cells support the unified hypothesis trying to relate DS, trisomy 21, and AD.